2014
DOI: 10.1007/978-1-62703-761-7_7
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Application of Triple Helix Forming Oligonucleotides and Single Strand Oligonucleotide Donors for Gene Correction

Abstract: Strategies for site-specific modulation of genomic sequences in mammalian cells require two components. One must be capable of recognizing and activating a specific target sequence in vivo, driving that site into an exploitable repair pathway. Information is transferred to the site via participation in the pathway by the second component, a donor nucleic acid, resulting in a permanent change in the target sequence. We have developed biologically active triple helix forming oligonucleotides (TFOs) as site-speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Based on DNA single fiber analysis [147] conducted by spreading and/or combing of DNA extracted from human cells following the induction of ICLs by the photoactivation of biotin-labeled psoralens [183][184][185], the groups of Seidman and Wang suggested that the major pathway involved in replication-associated ICL repair depends on a FANCM-mediated ICL traverse [146]. A single-molecule analysis allowed them to observe that, in the large majority of cases, the fork encountering an ICL was able to "traverse" it without repairing the lesion (Figure 3C).…”
Section: Third Icl Repair Model: Icl Traversementioning
confidence: 99%
“…Based on DNA single fiber analysis [147] conducted by spreading and/or combing of DNA extracted from human cells following the induction of ICLs by the photoactivation of biotin-labeled psoralens [183][184][185], the groups of Seidman and Wang suggested that the major pathway involved in replication-associated ICL repair depends on a FANCM-mediated ICL traverse [146]. A single-molecule analysis allowed them to observe that, in the large majority of cases, the fork encountering an ICL was able to "traverse" it without repairing the lesion (Figure 3C).…”
Section: Third Icl Repair Model: Icl Traversementioning
confidence: 99%
“…Nearly 30 years later, formation of DNA triplex was also reported 13 . Since then, the properties of triplexes have been intensively studied because they potentially offer attractive applications for engineering and therapeutic purposes 14 16 . The key feature of triplexes is that a third strand (referred to as Triplex Forming Oligonucleotide (TFO)) consisting of either a pyrimidine-rich or a purine-rich sequence, forms Hoogsteen (or reverse Hoogsteen) base pairs with a complementary purine-rich strand in the major groove of double-stranded DNA (dsDNA) without disrupting its canonical Watson-Crick base pairs.…”
Section: Introductionmentioning
confidence: 99%